A vivência do desalento entre jovens graduados: uma aproximação histórico-cultural - Paulino, Daniele de Souza (2021)
Youth unemployment is a constant in Brazil and in the world. In general, youth is the category most sensitive to economic crises, as well as the most exposed to the reality of unemployment and informality. In this context, discouragement, that is, giving up for looking for an occupation, reached 2.4 million young people aged between 18 and 29 in 2018, a number that tends to increase with the effect of the COVID-19 pandemic. However, although discouragement has always been present among the youth segment, the academic debate on the subject is still restricted to a statistical definition and propositions that point to investment in qualification, as an alternative for breaking with the condition. However, contrary to this perspective, the presence of discouragement among young people with higher education is a reality that points to the need to understand this phenomenon beyond its description. Therefore, from the scope of the cultural-historical theory (THC) in conjunction with some assumptions of cultural psychology, the general objective of this work is to investigate the experience (perejivânie) of discouragement in the face of the breach of expectations of the work idealized by young people with education higher. To achieve it, it is specifically intended: (a) to reconstruct the individual trajectory of the young person with regard to the sphere of work; (b) characterize the block of meaning in the face of discouragement and (c) apprehend the quadratic unit of meanings attributed by the young person in view of that break and the actions he develops to deal with that block. To this end, two case studies were carried out with young people in distress, by conducting five in-depth interviews with each of them, using the methodological strategy Trajectory Equifinality Model (TEM). The interviews were transcribed and, based on them, the trajectory of each participant was reconstructed, an element that allowed the analysis of the experience of each one's despondency when faced with the break of an idealized job. Finally, the findings are discussed in the light of (THC) and show that despondency goes beyond an economic definition, when referring to conflicts arising from career decisions in view of the break in idealization around work, experienced by young graduates. This finding, associated with the intervention carried out, has theoretical and practical implications for the area of professional guidance, above all, through the encouragement of exploratory behavior in professional careers.